Rewrite using a single positive exponent.
(4^-3)^7
7 answers
(4^-3)^7 = 4^(-3*7) = 4^-21
as a single positive
As a single positive exponent, (4^-3)^7 is equal to 4^(-3 * 7), which simplifies to 4^-21.
POSITIVE
Apologies for the confusion. To express (4^-3)^7 as a single positive exponent, we can multiply the exponents together since raising a power to another exponent is equivalent to multiplying the exponents.
(4^-3)^7 = 4^(-3 * 7) = 4^-21
(4^-3)^7 = 4^(-3 * 7) = 4^-21
I HATE YOU I KEEP SAYING POSITIVE AND YOU KEEP DOING NEGATIVE
I apologize for the misunderstanding. To express (4^-3)^7 with a single positive exponent, we need to multiply the exponents together, resulting in a positive exponent:
(4^-3)^7 = 4^(-3 * 7) = 4^-21
However, to rewrite this expression with a positive exponent, we can take the reciprocal of the base and change the sign of the exponent:
(4^-3)^7 = (1/4^3)^7 = (1/64)^7 = (1^7)/(64^7) = 1/64^7
Therefore, the expression (4^-3)^7 can be written as 1/64^7 with a positive exponent.
(4^-3)^7 = 4^(-3 * 7) = 4^-21
However, to rewrite this expression with a positive exponent, we can take the reciprocal of the base and change the sign of the exponent:
(4^-3)^7 = (1/4^3)^7 = (1/64)^7 = (1^7)/(64^7) = 1/64^7
Therefore, the expression (4^-3)^7 can be written as 1/64^7 with a positive exponent.